Speech-related auditory salience detection in the posterior superior temporal region - Erik C. Brown; Brittany Stedelin; Seiji Koike; Ahmed M. Raslan; Nathan R. Selden (NeuroImage, 2022)
Processing auditory human speech requires both detection (early and transient) and analysis (sustained). We analyzed high gamma (70–110 Hz) activity of intracranial electroencephalography waveforms acquired during an auditory task that paired forward speech, reverse speech, and signal correlated noise. We identified widespread superior temporal sites with sustained activity responding only to forward and reverse speech regardless of paired order. More localized superior temporal auditory onset sites responded to all stimulus types when presented first in a pair and responded in recurrent fashion to the second paired stimulus in select conditions even in the absence of interstimulus silence; a novel finding. Auditory onset activity to a second paired sound recurred according to relative salience, with evidence of partial suppression during linguistic processing. We propose that temporal lobe auditory onset sites facilitate a salience detector function with hysteresis of 200 ms and are influenced by cortico-cortical feedback loops involving linguistic processing and articulation.